Strategi Pengembangan Tanaman Sorgum (Sorghum bicolor) Menjadi Alternatif Pangan di Kabupaten Gunungkidul - Rohman, Nusron Habibur; Mustofa, Windy; Rohmaddoni, Novia; Puspitasari, Nia (Universitas Galuh, 2025)
This research aimed to determine the potential of sorghum with other food commodities, the condition of internal and external factors of sorghum, and alternative strategies that can be implemented in Gunungkidul Regency. This research uses a basic analytical descriptive method. The research location is Semin, Tepus and Wonosari Districts, Gunungkidul Regency. The informants were determined purposively. The data analysis used was the SWOT Matrix Method. The SWOT matrix produces eight alternative strategies that can be implemented in Gunungkidul Regency. These strategies include expansion of planting areas and guidance from the government, guidance on processing sorghum seeds into processed products, holding business meetings with investors for large-scale sorghum processing, regular counseling and guidance on good sorghum cultivation, providing training and post-harvest technology assistance, collaboration with the processing industry food, the role of government in determining selling prices and promotion of sorghum, increasing interaction between researchers, extension workers, marketers, policy makers and farmers.